The Worcester Fragments: a paleographical examination - Nyikos, EI (2017)
The Worcester Fragments represent the largest extant collection of polyphonic music from thirteenth-century England, with over a hundred compositions (many of them unica) across more than sixty manuscript fragments. Musicologists have known about the fragments for over a century, but the majority of their attention has been devoted to the remnants of one volume with surviving medieval foliation. Moreover, the tendency has been to conflate the many fragments into one ‘Worcester Repertory’ as though they represent the output of a single scriptorium at one point in time, with the result that the connections between the individual sources and the differences in manuscript production and musical repertory that they represent have been incompletely examined in scholarship.